Age-Related Transcriptional Deregulation of Genes Coding Synaptic Proteins in Alzheimer's Disease Murine Model: Potential Neuroprotective Effect of Fingolimod - Jęśko, Henryk; Wieczorek, Iga; Wencel, Przemysław Leonard; Gąssowska-Dobrowolska, Magdalena; Lukiw, Walter J.; Strosznajder, Robert Piotr (Frontiers in Molecular Neuroscience, 2021)
Alzheimer’s disease (AD) induces time-dependent changes in sphingolipid metabolism, which may affect transcription regulation and neuronal phenotype. We therefore analyzed the influence of age, amyloid  precursor protein (APP) and the clinically approved, bioavailable sphingosine-1-phosphate receptor modulator FTY720 on the expression of synaptic proteins. RNA was isolated, reverse-transcribed, and subjected to real-time PCR. Expression of mutant (V717I) APP led to few changes at 3 months of age, but reduced multiple mRNAs coding for synaptic proteins in 12 months old mouse brain. Complexin (Cplx1), SNAP25 (Snap25), syntaxin (Stx1a), neurexin (Nrxn1), neurofilament light (Nefl) and synaptotagmin (Syt1) in the hippocampus, and VAMP1 (Vamp1) and neurexin (Nrxn1) in the cortex were all significantly reduced in 12 month old mice. Postmortem AD samples from human hippocampus and cortex displayed lower expression of VAMP, synapsin, neurofilament light (NF-L) and synaptophysin. The potentially neuroprotective FTY720 reversed most APP-induced changes in gene expression (complexin, syntaxin, SNAP25, neurexin) in 12 month old hippocampus, which is thought to be the most sensitive to early neurotoxic insults, but it only restored Vamp1 in the cortex and had no influence in 3 months old brains. Further work may reveal the potential usefulness of FTY720 in the modulation of deregulated neuronal phenotype in AD brains.